Dictionary of the New Testament use of the Old Testament - Beale, G. K.; Carson, D. A.; Gladd, Benjamin L.; Naselli, Andrew David (Baker Academic, 2023)
Intro -- Half Title Page -- Title Page -- Copyright Page -- Contents -- List of Articles -- Articles by Topic -- Contributors -- Introduction -- Abbreviations -- Dictionary Articles -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- W -- Z -- Index of Scripture and Other Ancient Writings -- Cover Flaps -- Back Cover.